2021
DOI: 10.2147/jmdh.s334620
|View full text |Cite
|
Sign up to set email alerts
|

Bandura’s Self-Efficacy Model Used to Explore Participants’ Experiences of Health, Lifestyle, and Work After Attending a Vocational Rehabilitation Program with Lifestyle Intervention – A Focus Group Study

Abstract: Purpose We aimed to use the self-efficacy model to examine the participants’ experience, attitudes, and viewpoints regarding the association between work, health and lifestyle factors that influence work participation after completing a new one-year multidisciplinary vocational rehabilitation (VR) programme with a lifestyle intervention for people on or at risk of sick leave due to obesity or obesity-related problems. Materials and Methods This case study was based on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…These techniques involve training individuals to identify, approach, and resolve problems more effectively, thereby reducing stress and improving their ability to cope with challenging situations [43][44][45][46][47]. Bandura's (1986) thesis on selfefficacy and Beck's (2003) work on cognitive therapy underscore the importance of these techniques in enhancing problem-solving abilities and consequently reducing psychological distress, particularly depression [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…These techniques involve training individuals to identify, approach, and resolve problems more effectively, thereby reducing stress and improving their ability to cope with challenging situations [43][44][45][46][47]. Bandura's (1986) thesis on selfefficacy and Beck's (2003) work on cognitive therapy underscore the importance of these techniques in enhancing problem-solving abilities and consequently reducing psychological distress, particularly depression [48,49].…”
Section: Introductionmentioning
confidence: 99%
“…It also leads to greater commitment to rehabilitation procedures and more active participation in treatment procedures. This is particularly relevant for caring for patients with polytrauma associated with upper limb and chest injuries [11].…”
mentioning
confidence: 99%
“…A Norwegian study has recently shown impressive long-term results on work-related SE, HRQOL and weight-loss of vocational rehabilitation among obese workers at risk of sick leave. The intervention was "focusing on the workplace, cognitive approaches to develop skills for coping strategies, lifestyle change purposing BMI reduction, physical activity, and support from the surroundings" (Linge et al, 2021a;. In our study the most frequent goals were weight loss, psychological wellbeing, partner relationship and work situation (paper II),.…”
Section: Overweightmentioning
confidence: 77%
“…Using this understanding as a frame to support the patients' intrinsic motivation and SE seems fundamental to improve the patients' control of outcome (Lee et al, 2019). The value of using these theories in practice is recently confirmed by a Norwegian longitudinal study on overweight workers, who reached a great weight loss parallel to improvement in HRQOL (Linge et al, 2021a;.…”
Section: Future Use Of Health Theoriesmentioning
confidence: 96%
See 1 more Smart Citation